Insights into friction dependence of carbon nanoparticles as oil-based lubricant additive at amorphous carbon interface. (September 2019) - Li, Xiaowei; Xu, Xiaowei; Zhou, Yong; Lee, Kwang-Ryeol; Wang, Aiying
Abstract: Solid-liquid lubricating system, composed of amorphous carbon (a-C) and fluid lubricant, arouses enormous interest due to its excellent tribological performance. However, the friction response of a-C induced by carbon nanoparticles including graphene (G), fullerene (C60), and carbon nanotube (CNT) as oil-based additives and the underlying friction mechanism in synergism with base oil are unclear. Herein, using reactive molecular dynamics simulation, we comparatively investigated the friction dependence of G, C60, and CNT additives at the a-C interface. Compared with pure base oil, G results in the friction coefficient reduced by 90%, which exhibits the best anti-friction ability than C60 and CNT. The interfacial structure transformation, the interaction between the a-C, base oil, and additives, and the mobility of base oil indicate that being different with C60 or CNT which cross-links both the mating a-C surfaces, the G only anchors to one a-C surface to form a block physical protective film, which significantly smooths a-C surface, weakens the intermolecular interaction of a-C with base oil, and thus promotes the mobility of oil molecules, presenting a synergistic effect on the friction performance. These address the fundamental understanding on carbon additive-induced friction mechanism, and guide the design of a-C/lubricant composite system for tribological applications. Graphical abstract: Image 1